Case Study Pengembangan Kesehatan untuk Masyarakat Global Dimensi Masyarakat terhadap Kerusakan Alam Studi Bibliometrik dan Literatur Review - Sari, Wa Ode Ratnasari (Universitas Sulawesi Barat, 2025)
Introduction: Climate change and natural disasters have significant impacts on public health, especially related to gender inequality. This study aims to explore the gender dimension in the context of natural disaster damage. Objective: This study aims to conduct a bibliometric study and systematic literature review on the impact of natural disasters based on gender, and to produce inclusive health policy recommendations. Method: The Systematic Literature Review (SLR) method was used to identify and analyze 40 articles from international publications related to this topic, following the PRISMA guidelines. Bibliometric analysis as a data processor analyzed using VOS-Viewer software. Journal sources from ScienceDirect, MDPI, Springer, and Sage, Semantic scholar, Google Scholar were taken as researcher references. Article findings from 2013-2025. Results: The results show that women are more vulnerable to the impact of disasters, experience higher psychological trauma, and have difficulty accessing health services. Statistical analysis confirms significant differences in the impact of disasters based on gender. Conclusion: This study shows the importance of integrating gender dimensions in public health policies.